The Possibilities of Ultrasound in the Diagnosis of Congenital Dysplasia of the Hip Joint - Nozima Salieva1, Umida Rustamova2, Sarvinoz Rakhmanova3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Hip dysplasia is still the most common pathology in the structure of orthopedic pathology in children, andits diagnosis is difficult, and even with timely diagnosis, treatment does not always bring success, we werefaced with the task of optimizing radiation diagnosis of this pathology based on assumptions about themultiple etiological nature of dysplasia.To solve this problem, we selected 75 children from our ultrasound clinic. There were 52 girls and 23 boyswith an average age of 14 weeks.. Based on the ultrasound study, a technique has been developed to assessthe degree of maturity of the skeleton. Ultrasonic standards for the structure of the hip joints for childrenliving in the iodine-deficient region have been developed. Ultrasound signs of somatic, orthopedic andneurogenic forms of hip dysplasia were revealed.